Synthesis of polycaprolactone using free/supported enzymatic and non-enzymatic catalysts - Foresti, María Laura; Ferreira, María Luján (Macromolecular Rapid Communications)
Polymerization of caprolactone using lipases from Candida antarctica B, Rhizomucor meihei, Candida rugosa, and Pseudomonas fluorescens is highly effective, with 97% conversion into polycaprolactone. Poly(propylene)-supported Candida rugosa lipase achieves higher conversion values (85-92%) than free lipase (75%). Acidic and basic non-conventional catalysis with butanol yields 50-85% conversion. Simple UV/visible techniques gave the same results for measuring conversion than other studies. Applications are opened for the non-conventional catalysts. Fil: Foresti, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Ferreira, María Luján. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina